2011
DOI: 10.1111/j.1551-2916.2011.04655.x
|View full text |Cite
|
Sign up to set email alerts
|

High Temperature Infrared Properties of YSZ Electrolyte Ceramics for SOFCs: Experimental Determination and Theoretical Modeling

Abstract: Infrared radiative properties of 8-mol%-yttria-stabilized zirconia (8YSZ) ceramics of porosity 3% as applied as electrolyte for solid oxide fuel cells (SOFCs) were studied at room and elevated temperatures in the wavelength range from 2 to 20 lm. The room-temperature directional-hemispherical measurements of reflectance and transmittance for thin samples were combined with normal emittance measurements at several temperatures up to 1700 K. The use of the radiation transfer theory in a region of semi-transparen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 54 publications
0
20
0
1
Order By: Relevance
“…The experimental technique of this type is widely used in studies of semitransparent dispersed materials. Therefore, we do not reproduce here the experimental setup schematics, which can be found elsewhere [18][19][20][21]. The spectral measurements in the wavelength range of 0.67 ≤ λ ≤ 1.1 μm are analyzed in this paper.…”
Section: Samples and Experimental Proceduresmentioning
confidence: 99%
“…The experimental technique of this type is widely used in studies of semitransparent dispersed materials. Therefore, we do not reproduce here the experimental setup schematics, which can be found elsewhere [18][19][20][21]. The spectral measurements in the wavelength range of 0.67 ≤ λ ≤ 1.1 μm are analyzed in this paper.…”
Section: Samples and Experimental Proceduresmentioning
confidence: 99%
“…5 Doping ZrO 2 with Y 2 O 3 stabilizes either the cubic or tetragonal phase (strongly depending on production technique) over a large temperature range and creates oxygen vacancies. 2,3 Thus, a lot of progress has been made especially regarding characterization of the surface chemistry of a variety of different ZrO 2 samples. Materialwise, this essentially refers to supported metal/oxide systems 69 and sulfated ZrO 2 samples.…”
Section: Introductionmentioning
confidence: 99%
“…P OROUS zirconia ceramics have many advantages, such as low thermal conductivity, low density, corrosion resistance, and high-temperature resistance, 1,2 and so can be applied in many fields, namely ceramic filters, catalyst supports, solid oxide fuel cells, biological materials, and thermal barriers. [3][4][5][6][7] For thermal isolation use, research has been recently focused on zirconia thermal barrier coatings (TBC), [8][9][10][11] but few studies have reported the application of porous zirconia ceramics in bulk thermal isolators. 12,13 This is mainly because porous zirconia ceramics have a critical shortcoming, low strength, which seriously limits their application.…”
Section: Introductionmentioning
confidence: 99%